Inhibition of Histone Deacetylases Attenuates Morphine Tolerance and Restores MOR Expression in the DRG of BCP Rats - He, Xiao-Tao; Zhou, Kai-Xiang; Zhao, Wen-Jun; Zhang, Chen; Deng, Jian-Ping; Chen, Fa-Ming; Gu, Ze-Xu; Li, Yun-Qing; Dong, Yu-Lin (Frontiers in Pharmacology, 2018)
The easily developed morphine tolerance in bone cancer pain (BCP) significantly hindered its clinical use. Increasing evidence suggests that histone deacetylases (HDACs) regulate analgesic tolerance subsequent to continuous opioid exposure. However, whether HDACs contribute to morphine tolerance in the pathogenesis of BCP is still unknown. In the current study, we explored the possible engagement of HDACs in morphine tolerance during the pathogenesis of BCP. After intra-tibia tumor cell inoculation (TCI), we found that the increased expression of HDACs was negatively correlated with the decreased expression of MOR in the DRG following TCI. The paw withdrawal threshold (PWT) and percentage maximum possible effects (MPEs) decreased rapidly in TCI rats when morphine was used alone. In contrast, the concomitant use of SAHA and morphine significantly elevated the PWT and MPEs of TCI rats compared to morphine alone. Additionally, we found that SAHA administration significantly elevated MOR expression in the DRG of TCI rats with or without morphine treatment. Moreover, the TCI-induced increase in the co-expression of MOR and HDAC1 in neurons was significantly decreased after SAHA administration. These results suggest that HDACs are correlated with the downregulation of MOR in the DRG during the pathogenesis of BCP. Inhibition of HDACs using SAHA can be used to attenuate morphine tolerance in BCP.